Industrial Design Innovation of Sarawak Contemporary Furniture Design - Muhammad Firdaus, Abong Abdullah; Sharifah Emme Suzaimi, Syed Mohd Zahari; Mastika, Lamat (Elsevier Science Ltd., 2013)
This paper is part of a fundamental research on indigenous Dayak's motif of Sarawak as part of innovative design element for a contemporary chair design. Reviews of existing study on relation between novel, augmented, and copied designis used as a basis for establishing a distinctive Sarawak image in the Malaysian furniture industry through the approach of methodology of industrial design. The research opportunities are focus on a number of significant disparities that have restricted the development of competitive furniture designs from Sarawak in particular. These disparities include the manufacturers’ unfamiliarity with innovative design approach, a lack of understanding on the importance of good design, uncertainty on user needs, and inappropriate use of critical design elements. The introduction of pioneered material species; despite providing new alternative to materials, adds further disparities to new furniture design and development as more resources will need to be allocated for design management, development, testing and validation. This article provides an academic perspective on the contribution of industrial design to both innovation and performance. This perspective can be referred and adapted by the furniture industry player in Sarawak to establish a formal furniture design framework that emphasis industrial design, which could enable them to compete in the local and international market.